The Influence of Collaborative Supervision on Enhancing Self-Efficacy and Teaching Performance of Islamic Education Teachers at MAN 2 Tanah Datar - Jamilus; Vicky Rizki Febrian (Yayasan Darusssalam Bengkulu, 2026)
This study aims to analyze the effect of collaborative supervision on teachers’ Self-efficacy and teaching performance of Islamic Education (PAI) teachers at MAN 2 Tanah Datar, as well as to examine the relationship between Self-efficacy and teaching performance. This research employed a quantitative approach with an ex post facto associative design using Structural Equation Modeling (SEM). The sample consisted of all PAI teachers selected through total sampling technique. Data were collected using Likert-scale questionnaires that had been tested for validity and reliability. The findings indicate that collaborative supervision has a significant positive effect on Self-efficacy (β = 0.67) and teaching performance (β = 0.54). Furthermore, Self-efficacy has a strong positive relationship with teaching performance (β = 0.71). These results imply that collaborative supervision plays a crucial role in enhancing both the psychological and professional aspects of teachers. It is recommended that school leaders implement continuous and participatory supervision strategies to improve teacher performance and educational quality.